(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The fifth generation of broadband wireless telecommunications will increase the speeds of upload and download with decreasing the access network latency and enable bandwidth in excess of 100s of Megabits per second (Mb/s) with latency of less than 1 millisecond (ms), as well as provide access network to billions of subscribers. In this paper the innovations and challenges of 5G are described such as mm-waves, small cells, Massive MIMO, Beamforming, Full Duplex FD, Non-Orthogonal Multiple Access NOMA, and Mobile Edge Computing MEC. The results show that the millimeter waves development is the dominant innovation of 5G technology, which increases the data traffic 1000 times more data than 4G and offer manufacturing of products with cheaper prices. It is concluded that 5G, represents a big step forward in increasing the flexibility of the network infrastructure, and improve scalability and service. Also 5G is not limited to telecommunication services but it represents the Beyond technology in research, automotive, energy, e-business, e-government, vertical industry, security, e-Health, improving human being’s life. 5G will be the future benchmark of smart city.